Strength training and neural activiation - Gollhofer, A.
1. "General" Strength Training is likely to give unspecific results and hence doubtful 2. Recommended is "Specific" Strength Training to achieve highly specific results as needed in the various sports or events 3. Adaptation is load dependend and 4. Adaptation is highly specific 5. To be effective and efficient : Few repetitions . high intensity [ . 80 . 101% ] 6. To be accurate and effective biomechanical support is recommended